Effects of Agriculture on Climate Change: A Cross Country Study of Factors Affecting Carbon Emissions - Pant, Krishna Prasad (Journal of Agriculture and Environment, 2009)
Agriculture affects atmosphere by releasing green house gases and get affected in turn, from climate change. This paper reviews the literature on both the aspects and test empirically that what affects emissions of carbon dioxide to the atmosphere. Data on carbon emissions, energy consumption and agriculture related national level variables are obtained for 120 countries from the World Bank's Green Data Book. Multiple linear regression analysis revealed that agricultural land, irrigation, forest area, biomass energy, and energy use efficiency negatively affect the Carbon dioxide emission. But, fertilizer use and per capita energy use affect it positively. The analysis confirms that the people in rich countries are more responsible for carbon emission than the people in poor countries. It recommends for cross subsidization for low external input agriculture, particularly for organic farming in poor countries. Key words : Agriculture; Carbon emissions; Climate change; Energy consumption; GHGs The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 84-102